Foreign Body Bronchus and Rigid Bronchoscopy– Our Experiences at a Tertiary Care Hospital - Santosh Kumar Swain1 , Surya Kanta Pradhan2 , Sanjeev Gupta2 , Kamalakanta Jena2 , Priyanka Debta3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Foreign body inhalation is often encountered in emergency department. Foreign body can belodged in any site of the tracheobronchial air way. Rigid bronchoscopy is one of the established techniquefor removal of the inhaled foreign body with fewer complications.Material and Method: We have done a retrospective study in our tertiary care center to determine theclinical presentation, nature of foreign body, age of presentation, location of foreign body, management offoreign bodies and duration of hospital stay in our population.Result: The most common foreign body in our study was peanut(15.7%) followed by ground nut (12.2%),coconut pieces (7%), small led bulbs (7%) and corn (7%).Most common sites for foreign body lodgment wasright main bronchus (40.3%) followed by left main bronchus (29.8%) and trachea (17.5%).Conclusion: Rigid bronchoscopy is an effective technique for removal of the foreign body fromtracheobronchial airway with fewer complications.